Inception and philosophy : because it's never just a dream - Johnson, David Kyle (Blackwell philosophy and popculture series., 2012)
A philosophical look at the movie Inception and its brilliant metaphysical puzzles Is the top still spinning? Was it all a dream? In the world of Christopher Nolan's four-time Academy Award-winning movie, people can share one another's dreams and alter their beliefs and thoughts. Inception is a metaphysical heist film that raises more questions than it answers: Can we know what is real? Can you be held morally responsible for what you do in dreams? What is the nature of dreams, and what do they tell us about the boundaries of "self" and "other"? From Plato to Aristotle and from Descartes to Hu.